2015
DOI: 10.7196/sajch.7941
|View full text |Cite
|
Sign up to set email alerts
|

Severe pneumonia in HIV-infected and exposed infants in a paediatric ICU

Abstract: Within South Africa (SA) (as in many other countries), HIV infection is a significant cause of morbidity in women and their infants. In SA, 26% of pregnant women are HIV-infected, and in the absence of preventive therapy there is a 15-30% risk of HIV infection in their infants. [1,2] Even children who are part of the prevention of motherto-child transmission (PMTCT) programme have an increased risk of HIV-related infection relative to those who are not exposed, although that risk is substantially reduced. Mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The overall mortality was in keeping with recent studies which have shown an improvement in survival from 32% to 35% in the early 1990s to 82% to 90% in 2009 -2011. [15,[18][19][20] However, although it was still slightly higher than that found in high-income countries where overall PICU mortality averages 6%, it is in keeping with their mortality rates for serious bacterial infections and pneumonia (~17.5% in children). [19][20][21] The median PICU length of stay was 8 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall mortality was in keeping with recent studies which have shown an improvement in survival from 32% to 35% in the early 1990s to 82% to 90% in 2009 -2011. [15,[18][19][20] However, although it was still slightly higher than that found in high-income countries where overall PICU mortality averages 6%, it is in keeping with their mortality rates for serious bacterial infections and pneumonia (~17.5% in children). [19][20][21] The median PICU length of stay was 8 days.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] As a result, HIV-exposed uninfected (HIV-EU) babies now account for as many as 30% of all births in parts of southern Africa. [9,14,15] However, the effect of HIV exposure on pneumonia morbidity and mortality risk is less well known. They are nevertheless considered a vulnerable population and appear to have an increased morbidity and mortality rate from infections when compared with their HIV-unexposed (HIV-U) counterparts.…”
mentioning
confidence: 99%